Child Maltreatment and Risky Sexual Behavior: Indirect Effects Through Trauma Symptoms and Substance Use. (February 2017) - Thompson, Richard; Lewis, Terri; Neilson, Elizabeth C.; English, Diana J.; Litrownik, Alan J.; Margolis, Benyamin; Proctor, Laura; Dubowitz, Howard
Risky sexual behavior is a serious public health problem. Child sexual abuse is an established risk factor, but other forms of maltreatment appear to elevate risky behavior. The mechanisms by which child maltreatment influence risk are not well understood. This study used data from 859 high-risk youth, followed through age 18. Official reports of each form of maltreatment were coded. At age 16, potential mediators (trauma symptoms and substance use) were assessed. At age 18, risky sexual behavior (more than four partners, unprotected sex, unassertiveness in sexual refusal) was assessed. Neglect significantly predicted unprotected sex. Substance use predicted unprotected sex and four or more partners but did not mediate the effects of maltreatment. Trauma symptoms predicted unprotected sex and mediated effects of emotional maltreatment on unprotected sex and on assertiveness in sexual refusal and the effects of sexual abuse on unprotected sex. Both neglect and emotional maltreatment emerged as important factors in risky sexual behavior. Trauma symptoms appear to be an important pathway by which maltreatment confers risk for risky sexual behavior. Interventions to reduce risky sexual behavior should include assessment and treatment for trauma symptoms and for history of child maltreatment in all its forms.